Engineering quantum control with optical transitions induced by twisted light fields - Zanon-Willette, Thomas (2024)
A form of quantum control is proposed by applying twisted light, also known as optical vortex beams, to drive ultranarrow atomic transitions in neutral Ca, Mg, Yb, Sr, Hg, and Cd bosonic isotopes. This innovative all-optical spectroscopic method introduces spatially tailored electric and magnetic fields to fully rewrite atomic selection rules, reducing simultaneously probe-induced frequency shifts and additional action of external ac and dc field distortions. A twisted-light focused probe beam produces strong longitudinal electric and magnetic fields along the laser propagation axis, which opens the S01→P03 doubly forbidden clock transition with a high E1M1 two-photon excitation rate. This long-lived clock transition is thus immune to nonscalar electromagnetic perturbations. Zeeman components of the M2 magnetic quadrupole S01→P23 transition considered for quantum computation and simulation are now selectively driven by transverse or longitudinal field gradients with vanishing electric fields. These field gradients are manipulated by the mutual action of orbital and spin angular momentum of the light beam and are used in presence of tunable vector and tensor polarizabilities. A combination of these two different twisted-light induced clock transitions within a single quantum system, at the same magic wavelength and in presence of a common thermal environment, significantly reduces systematic uncertainties. Furthermore, it generates an optical synthetic frequency which efficiently limits the blackbody radiation shift and its variations at room temperature. Engineering light-matter interaction by optical vortices merged with composite pulses will ultimately benefit experimental atomic and molecular platforms targeting an optimal coherent control of quantum states, reliant quantum simulation, novel approaches to atomic interferometry, and precision tests of fundamental theories in physics and high-accuracy optical metrology.